2018
DOI: 10.1038/s41391-018-0035-z
|View full text |Cite
|
Sign up to set email alerts
|

Combining immune check-point blockade and cryoablation in an immunocompetent hormone sensitive murine model of prostate cancer

Abstract: Trimodal therapy consisting of androgen deprivation, cryoablation and PD-1 blockade, as well as the combination of cryoablation and low dose anti-CTLA-4 blockade showed that local therapies with cryoablation could be considered to augment the effects of checkpoint blockade in prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The development of biology is helpful in finding therapeutic targets for diseases [27]. Biomedicine has made great progress in cancer treatment [28]. Recent studies have shown the success of using inhibitory peptides to disrupt specific protein-protein interactions and their pertinent biological events [2932].…”
Section: Introductionmentioning
confidence: 99%
“…The development of biology is helpful in finding therapeutic targets for diseases [27]. Biomedicine has made great progress in cancer treatment [28]. Recent studies have shown the success of using inhibitory peptides to disrupt specific protein-protein interactions and their pertinent biological events [2932].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of combinations of cryotreatment and immune checkpoint inhibitors have been reported [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Co-stimulation of the immune system with tumor antigens via cryosurgery in the presence of a “primed” immune system, pretreated with CTLA-4 and PD-1 combination therapy, would theoretically result in a synergistic effect of local tumor and distant metastasis regression or an abscopal effect [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effect of a combination of cryotreatment and immunotherapy has been reported [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In these basic and clinical research, cytotoxic T-lymphocyte-associated protein (CTLA-4) and programmed death-1 (PD-1) antagonists play a complementary role in the activation of cancer immunity, and immunotherapy followed by cryosurgery could demonstrate to induce a more cancer-specific immune response to distant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer (PCa) is the most common cancer in males and the second leading cause of cancer death [1,2]. Until now, available therapies for advanced stages of this disease are still limited, and their effectiveness is far from satisfactory.…”
Section: Introductionmentioning
confidence: 99%